Spoken Interlanguage Errors In Microteaching Class Made By Students Of English Department Of Muhammadiyah University Of Surakarta - Ernasari, Devi, Prof. Endang Fauziati, Siti Fatimah S.Pd., M.Hum (2015)
SUMMARY Devi Ernasari. A320110040. SPOKEN INTERLANGUAGE ERRORS IN MICROTEACHING CLASS MADE BY STUDENTS OF ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA. Muhammadiyah University of Surakarta. Research Paper 2015. This research paper is aimed to classify the type of errors, analyze the frequency and dominant, and explain the sources of error. The type of this research is qualitative research. The research collects micro teaching video from her friends. The research makes the transcript of the video as the source of the data. The research uses documentation method to select the data. There are 356 data containing of errors. The research uses Clark and Clark theory and Dulay, Burt, and Krashen theory to analyze the errors. The research divided the errors found into three classifications. They are speech error, morphological error and syntactical error. In speech errors are filled pause (32,02%), repeats (23,88%), silent pause (17,13%), correction (6,18%), stutters (1,97%), interjection (1,69%), retraced (1,40%), and slip of tongue (1,12%). Morphological error are vocabulary error (5,90%), pronunciation error (2,25%), ommision of bound morpheme {-s} as singular marker (1,69%), ommision of bound morpheme {-s} as plural marker (1,12%), and error in word selection (1,12%). Syntactical error is the use of V-ing after modals Auxiliary (1,41%) and ommision of definite preposition (1,12%). The sources of error are cognitive, psychological and social reason. Keyword: Interlanguage, Error Analysis, Microteaching